2021
DOI: 10.1101/2021.07.18.452824
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic mechanisms of CRISPR interference by Escherichia coli CRISPR-Cas3

Abstract: Type I CRISPR-Cas3 uses an RNA-guided multi Cas-protein complex, Cascade, which detects and degrades foreign nucleic acids via the helicase-nuclease Cas3 protein. Despite many studies using cryoEM and smFRET, the precise mechanism of Cas3-mediated cleavage and degradation of target DNA remains elusive. Here we reconstitute the CRISPR-Cas3 system in vitro to show how the Escherichia coli Cas3 (EcoCas3) with EcoCascade exhibits collateral non-specific ssDNA cleavage and target specific DNA degradation. Partial … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 75 publications
(191 reference statements)
0
6
0
Order By: Relevance
“…In summary, we have shown that CONAN, a Cas3-based novel in vitro nucleic acid-detection platform, is a rapid (within 30-40 min), low-cost, and instrument-free detection method for SARS-CoV-2. We also showed that this CONAN-based assay enables single-base-pair discrimination (Figures 2F and 2G) (Yoshimi et al, 2021), thereby facilitating the deployment of CRISPR-dx for quick and mobile POCTs for drug-resistant IAV variants in hospitals or clinics.…”
Section: Conan-based Assay For Rapid Detection Of Sars-cov-2 and Infl...mentioning
confidence: 78%
See 4 more Smart Citations
“…In summary, we have shown that CONAN, a Cas3-based novel in vitro nucleic acid-detection platform, is a rapid (within 30-40 min), low-cost, and instrument-free detection method for SARS-CoV-2. We also showed that this CONAN-based assay enables single-base-pair discrimination (Figures 2F and 2G) (Yoshimi et al, 2021), thereby facilitating the deployment of CRISPR-dx for quick and mobile POCTs for drug-resistant IAV variants in hospitals or clinics.…”
Section: Conan-based Assay For Rapid Detection Of Sars-cov-2 and Infl...mentioning
confidence: 78%
“…Cascade/Cas3 and Cas12a target sites were based on the human EMX1 gene, the mouse Tyr gene, and the N gene from SARS-CoV-2 (Table S1). A baculovirus expression system was used to purify the EcoCas3 protein, as previously shown (Yoshimi et al, 2021). Briefly, EcoCas3 cDNA was cloned using an octa-histidine tag and a six asparagine-histidine repeat tag into pFastbac-1 plasmids.…”
Section: Methods Details Crispr Preparationmentioning
confidence: 99%
See 3 more Smart Citations